Eliminate Hazards in Your Home: A Safety Checklist With Recommendations - Maria van Zuilen; Osvaldo Rodriguez; Michael Mintzer (Association of American Medical Colleges, 2008)
Abstract Each year, many older adults suffer accidental injuries in and around the home or are victims of crime in their home. Falls, fires, or burglaries can result in substantial injury or even death. This checklist is designed as a survey tool to be used during a home safety evaluation. It assesses various aspects of safety in and around the home. For each concern identified, one or more recommendations are provided for improving safety, many of which can be accomplished with little or no cost. A copy of the completed checklist is given to the person whose home has been evaluated. This checklist is designed for medical students, primary care residents, and other healthcare trainees and professionals who participate in the evaluation of older adults in the home. It is helpful if the learner has received basic instruction on home safety evaluation as this will help them complete a more in-depth assessment. The checklist items are linked to instructional content included in the home safety assessment training module developed by faculty in our program. This checklist can also be used as a patient education tool. At the University of Miami Miller School of Medicine, first year medical students (in pairs) complete three home visits with active older adults residing in the community. During their final visit they complete a home safety assessment using a home safety checklist. Subsequently each student independently completes an online report in which they answer several questions related to their elder's safety. One of the questions asks them to describe their elder's home environment and strategies to reduce fall risk. Students are instructed to include a description of specific environmental observations and modifications useful in reducing fall risk. This home visit has been part of the curriculum for eight years. Prior to 2005 students attended a one-hour lecture on home safety assessment before making the home visit. They used a pre-existing checklist which allowed them to check off problem areas; recommendations were provided on separate pages. For the past two years, students have used the home safety assessment training module as advance preparation for the home visit and this new checklist during their visit. To evaluate the effectiveness of the curricular changes, we compared the written reports of two cohorts: cohort 1 completed the curriculum immediately before revisions and cohort 2 received the new curriculum. To rate the written submissions, we developed a 33-item checklist containing a broad range of home-safety elements (e.g., handrails, throw rugs, stairs, lighting). We then marked whether one or both students in a pair (cohort 1 N = 75 and cohort 2 N = 86) commented on the presence or absence of the element, and whether they documented specific recommendations. The average number of elements documented in the reports increased from 4.8 to 8.2 and the average number of recommendations mentioned increased from 2.5 to 3.3.